Unraveling the Proteomic Landscape of Intestinal Epithelial Cell-Derived Exosomes in Mice - Ding, Zhenyu; Zhang, Cuiyu; Zhang, Baokun; Li, Qin (Frontiers in Physiology, 2022)
Abstract Purpose: This study aimed to identify the biological functions of small intestine IEC-Exos and further distinguished the difference proteins in IEC-Exos between ileum and jejunum related to function of the digestive system and occurrence of several diseases. Materials and Methods: IECs of Male C57BL/6J mice were isolated. IEC-Exos were extracted from jejunum and ileum epithelial cell culture fluid by ultracentrifugation. In addition, isobaric tags for relative and absolute quantitation (iTRAQ) combined with liquid chromatography-tandem mass spectrometry (LC-MS/MS) were used to detect IEC-Exo proteins and conduct biological information analysis. Results: The results showed that compared with jejunum IEC-Exos from ileum IEC-Exos, there were 393 up-regulated proteins and 346 down-regulated proteins. IECs-Exos, especially derived from jejunum, were rich in angiotensin-converting enzyme 2 (ACE2). The highly expressed proteins from ileum IEC-Exos were mostly enriched in genetic information processing pathways, which mainly mediate the processes of bile acid transport, protein synthesis and processing modification. In contrast, the highly expressed proteins from jejunum IEC-Exos were mainly enriched in metabolic pathways involved in sugar, fatty acid, amino acid, drug, and bone metabolism, etc. The differentially expressed proteins between ileum and jejunum IEC-Exos were not only related to the function of the digestive system but also closely related to the occurrence of infectious diseases, endocrine diseases and osteoarthritis, etc. Conclusions: IEC-Exos there were many differentially expressed proteins between ileum and jejunum, which played different roles in regulating intestinal biological functions. ACE2, the main host cell receptor of SARS-CoV-2, was highly expressed in IEC-Exos, which indicated that IEC-Exos may be a potential route of SARS-CoV-2 infection.